Development of a Thai university model oriented to working adults and the retired elderly - Prachyapruit, Apipa (Humanities, Arts and Social Sciences Studies, 2023)
Global demand for adult tertiary education is rising and many universities are adapting to answer this demand, including those in Thailand. Therefore, this study aims at developing a model for reorienting Thai universities towards working adults and retirees. This university reorientation model is derived from a synthesis of critical elements for university adult education and analysis of the current adult education practices of Thai universities alongside the good practices of universities abroad. Data were collected through documentary research, expert interviews, stakeholder interviews and expert validation. Results showed that firstly, elements important to university adult education orientation include external organizational context; institutional principles, philosophy and core values; education provision; student affairs; research and innovation development; academic services and cultural preservation; and administration. Secondly, it became apparent that Thai universities share some good practices with their counterparts abroad, including university philosophies that promote equality and diversity, lifelong learning infrastructures, partnership development, and a variety of flexible programs. Nevertheless, many Thai universities lack some of the good practices found elsewhere such as mature student service units, services tailored to adult client needs, financial aid for working adults and retirees, adult student associations, and university retirement communities. Thus, the reorientation model developed in this study consists of six elements: philosophy and mission; policy, partnerships, and organizational and administrative structure; education provision; student affairs; research and innovation development; and environment and technology.